The Roots of Modern Hollywood : the Persistence of Values in American Cinema, from the New Deal to the Present. - Smedley, Nick (Intellect, 2014)
In this insightful study of Hollywood cinema since 1969, film historian Nick Smedley traces the cultural and intellectual heritage of American films, showing how recentHollywood movies owe a profound debt to the liberal values of New Deal cinema. Hollywood cinema is not usually thought of as politically or socially engaged, but theauthor argues that it is, in fact, one of the most value-laden of all national cinemas. Drawing on a long historical view of persistent themes in Hollywood cinema, Smedleydemonstrates how film-makers in America continue to explore the balance between unbridled capita.